Education journals: a comparison of publishing patterns in Australian, German and English education journals - Mertova, Patricie [Verfasser]; Ertl, Hubert [Verfasser]; Zierer, Klaus [Verfasser] (My University, 2019)
"This paper compares the findings of two studies on the publication patterns in leading Australian, English and German education journals. The first study was funded by the German Research Association and the second one was unfunded, and they were conducted by a team of international researchers. The first study compared three English and three German leading education journals. The second study analysed the publication patterns in three leading Australian education journals. All papers published between 2001 and 2010 in the nine selected education journals were analysed according to their author profile, thematic focus and methodology used. The analyses (covering three geographical regions) showed the publication patterns in the selected journals, indicating similarities and also some key differences. This paper focuses on the Australian education journals and how their publication patterns relate to the English and German journals." (authors' abstract ; BIBB-Doku)
Keywords: I 2.3.5 Australien, Ozeanien; I 2.2.1 Westeuropa; I 2.1 Deutschland; Erziehungswissenschaft; Berufsbildungsforschung; Literaturanalyse; Zeitschrift; Vergleich; Australien; England; Bundesrepublik Deutschland